Burden of arrhythmia in hospitalizations with opioid overdose. (1st July 2019) - Doshi, Rajkumar; Shah, Jay; Desai, Rupak; Gullapalli, Nageshwara
Abstract: Background: Opioid overdose-related hospitalizations continue to rise in the United States. These hospitalizations are frequently associated with arrhythmia which can increase in-hospital mortality and resource utilization. We describe temporal trends in the hospitalizations for opioid overdose, associated arrhythmias, and their impact on in-hospital mortality, length of stay and cost of hospitalizations. The purpose of this study was to identify incidence of arrhythmia and their impact on in-hospital outcomes with opioid overdose hospitalizations. Methods: The study utilized data from the National Inpatient Sample from January 2005 to September 2015. Previously employed International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes were utilized to identify opioid overdose and associated arrhythmias. The analysis was performed using SAS (SAS Institute Inc., Cary, NC). Temporal trends were measured using Jonckheere-Terpstra Trend test. Results: A total of 430, 460 adult hospitalizations with opioid overdose were included in this study. Atrial fibrillation ( N = 17, 695, 4.1%) was the most frequent arrhythmia associated with opioid overdose, the trend of which increased significantly during the study period. All-cause in-hospital mortality increased substantially with arrhythmias, highest with ventricular fibrillation and ventricular tachycardia. The incidence of arrhythmias was associated with longer length of stay and higher cost of hospitalizations as well. Conclusions: Incidence of new-onset arrhythmia with opioid overdose lead to higher in-hospital mortality which can further increase the length of hospitalization and cost of care. Highlights: Arrhythmias associated with opioid overdose are increasing significantly. Atrial fibrillation is the most common arrhythmias associated with opioid overdose. These arrhythmias are associated with higher in-hospital mortality. These leads to higher resource utilization with longer stay and higher cost.